ZAKAT PAYMENT AWARENESS: A DETERMINAT STUDY - Ainun Mardhiah; Khalish Khairina; Uswatun Hasanah (Referensi Islamika: Jurnal Studi Islam, 2026)
The role of improving welfare is not only the government's obligation, but also the community. One of which is through the distribution of zakat. Zakat can be used to overcome social problems, so awareness in paying zakat is needed. Data analysis was conducted using CB-SEM via LISREL. The structural model incorporates accountability, knowledge, technology, and promotion as exogenous variables, with trust and commitment acting as intervening variables toward zakat awareness. Methodologically, data were analyzed using Covariance-Based SEM via LISREL with the Maximum Likelihood estimation. Through accidental sampling, 170 nisab-compliant Muslim residents participated as respondents, with their wealth status verified via preliminary screening questions. The research results show that, 1). The exogenous variable Accountability has a significant effect on commitment and does not have a significant effect on the level of trust. 2) The exogenous variable Knowledge has a significant influence on the level of trust and commitment. 3) The exogenous variable Technology does not have a significant effect on the level of trust and commitment variables. 4) The promotion variable does not have a significant effect on the level of trust and commitment variables. 5). The level of trust and commitment has a significant effect on people's awareness of paying Zakat in Baitul Maal. The finding that accountability has an effect on commitment while technology and promotion have no significant effect provides a new perspective for Baitul Mal to create more representative policies so that the community has more confidence and awareness in paying zakat at Baitul Mal. This research demonstrates that Baitul Mal Lhokseumawe must prioritize strengthening the accountability and knowledge of muzakki. However, technology and promotion are sometimes not always the primary drivers of zakat payments in the Lhokseumawe community.